(untitled) (Computer systems and information technologies, 2023)
number of accidents, researchers and engineers are constantly working on the introduction of new technologies. One of the significant innovations is the speed control system based on traffic cameras use. This paper gives a detailed overview of speed control systems role and importance on the roads. The principles of its operation, advantages, as well as methods of increasing the efficiency of this system in order to achieve optimal results in speed control and ensuring road safety are also analyzed in detail.